Crystal Deposition Disease and Psoriatic Arthritis - O'Connor, Philip J. (Seminars in Musculoskeletal Radiology, 2013)
To the practicing clinical radiologist, knowledge of the ultrasound appearances of crystal diseases is important. Assessment of bone or soft tissue changes related to rheumatoid arthritis is a rare clinical indication for ultrasound, whereas crystal diseases have a broad spectrum of presentations requiring clinical diagnostic imaging. Psoriatic arthritis is an entheseal disease with secondary joint involvement, where imaging findings include inflammatory enthesopathy with erosions as well as flexor tendon tenosynovitis. The ultrasound features of crystal deposition diseases and psoriatic arthritis in soft tissues and joints are relatively characteristic, and an awareness of these appearances is vital to the practicing musculoskeletal sonologist.
Keywords: gout; pseudogout; CPPD; psoriatic arthritis